2014
DOI: 10.1136/bmj.g3859
|View full text |Cite|
|
Sign up to set email alerts
|

Revascularisation versus medical treatment in patients with stable coronary artery disease: network meta-analysis

Abstract: Objective To investigate whether revascularisation improves prognosis compared with medical treatment among patients with stable coronary artery disease.Design Bayesian network meta-analyses to combine direct within trial comparisons between treatments with indirect evidence from other trials while maintaining randomisation.Eligibility criteria for selecting studies A strategy of initial medical treatment compared with revascularisation by coronary artery bypass grafting or Food and Drug Administration approve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
195
2
22

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(224 citation statements)
references
References 51 publications
5
195
2
22
Order By: Relevance
“…TVR occurred in 556 patients (5.61%). The risk of TVR was similar in patients randomly allocated to treatment with R-ZES compared with patients randomly allocated to treatment with EES (6 Figure 3C). TV-MI was observed in 325 patients (3.28%).…”
Section: Clinical Outcomesmentioning
confidence: 75%
See 2 more Smart Citations
“…TVR occurred in 556 patients (5.61%). The risk of TVR was similar in patients randomly allocated to treatment with R-ZES compared with patients randomly allocated to treatment with EES (6 Figure 3C). TV-MI was observed in 325 patients (3.28%).…”
Section: Clinical Outcomesmentioning
confidence: 75%
“…Notwithstanding, there remains residual uncertainty whether the 2 devices differ with respect to individual safety and efficacy outcomes, notably the risk of stent thrombosis (ST). Although several network meta-analyses compared different DES, [6][7][8][9] there was an inconsistency between direct and indirect evidence with regard to the effectiveness of R-ZES and EES. 8 Therefore, we sought to perform a pairwise meta-analysis of randomized clinical trials with direct comparisons of FDAapproved new-generation DES to evaluate the safety and efficacy of R-ZES and EES in patients undergoing PCI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 These trials include studies not only on the use of percutaneous coronary intervention (PCI), but also on coronary artery bypass graft surgery (CABG), medical therapy, and diagnostic technologies such as fractional flow reserve (FFR) to guide revascularization. [5][6][7][8] Additional studies, some based on data from the National Cardiovascular Data Registry (NCDR), have been published providing insights into practice patterns and information around clinical scenarios and patient features not previously addressed. [9][10][11][12][13] Improvements in our understanding of the variables affecting patient outcomes before and after coronary revascularization, continued emphasis on the role of medical therapy for coronary artery disease (CAD), and an increasing emphasis on shared decision making and patient preferences also make a revision of the coronary revascularization AUC timely.…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed improved survival with newer generation of drug-eluting stents when compared to medical therapy. 18 On the other hand, two additional meta-analyses comprising 7,200 and 8,000 patients found no difference in mortality in patients treated with PCI compared to optimal medical therapy. 19,20 The Fractional Flow Reserve Versus Angiography for Multivessel Evaluation 2 (FAME 2) trial examined patients with stable CAD for whom PCI was being considered.…”
Section: Evaluation Of Patients With Stable Cadmentioning
confidence: 99%